2005
DOI: 10.1055/s-2005-837775
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Hypoglycemic Effect of Stevioside, a Glycoside ofStevia rebaudiana

Abstract: We have studied the effects of stevioside on the glucose and insulin metabolism in 2 models of diabetes in rats, STZ-induced diabetic rats and NIDDM diabetic rats induced by feeding with fructose. Stevioside (0.5 mg/kg), lowered the blood glucose levels in STZ-induced diabetic rats, peaking at 90 min. Stevioside administered twice daily also demonstrated dose-dependent effects in lowering the glucose levels in both diabetic rat models. Stevioside reduced the rise in glucose during glucose tolerance testing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 11 publications
7
82
2
5
Order By: Relevance
“…A lesser increase in postprandial glycemia and the insulin index was observed in the group of individuals administered steviosides. Similar conclusions were presented by Taiwanese researchers, who investigated the effect of steviol glycosides on the metabolism of glucose and insulin in two groups of diabetic rats (Chen et al 2005). In the first group, hyperglycemia was induced using Streptozotocin, while in the other group diabetes was induced by administering fructose (insulin-dependent diabetes).…”
Section: Hypoglycemic Effectsupporting
confidence: 76%
“…A lesser increase in postprandial glycemia and the insulin index was observed in the group of individuals administered steviosides. Similar conclusions were presented by Taiwanese researchers, who investigated the effect of steviol glycosides on the metabolism of glucose and insulin in two groups of diabetic rats (Chen et al 2005). In the first group, hyperglycemia was induced using Streptozotocin, while in the other group diabetes was induced by administering fructose (insulin-dependent diabetes).…”
Section: Hypoglycemic Effectsupporting
confidence: 76%
“…In a similar study in 2000, Jeppesen et al showed that stevia derivatives by affecting pancreatic β-cells increase the insulin level and reduce blood glucose (31). As revealed by other researchers, the anti-diabetic effect of stevia and its glycoside might be exerted through the stimulation of peripheral glucose utilization or enhancement of glycolytic and glycogenic processes, concomitant with the decline in glycogenolysis and gluconeogenesis and glucose absorption in the duodenum (31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 96%
“…Chen et al showed that stevioside can regulate the blood glucose level not only by enhancing insulin secretion, but also by slowing down gluconeogenesis through reducing phosphoenolpyruvate carboxykinase gene expression in the rat liver, which in turn regulates the blood glucose level (35).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the low concentration of stevioside has an immense action in glucose transport in skeletal muscle. Chen et al (2005) suggested that stevioside enhances the insulin secretion and also helps in insulin utilisation by regulating blood glucose levels in insulin-deficient rats. It was due to the stevioside action of slowing down gluconeogenesis which decreases the phosphoenolpyruvate carboxykinase (PEPCK) gene expression in rats' liver.…”
Section: Glucoregulationmentioning
confidence: 99%